Il fantasma di Elena Spettri nella No Man’s Land - Amato, Pierandrea (Mechane, 2023)
The essay, beginning with a brief reading of Euripides’ tragedy, Helen (412 B.C.), considers war a spectral event in human existence. No less so when, with World War I, the physiognomy of the conflict takes on the terrible features of a technological carnage where man becomes nothing more than a material among others.